METHODS OF FORMING AND DEVELOPING SKILLS RELATED TO TECHNICAL MECHANICS IN ENGINEERING STUDENTS (American Journal of Technology and Applied Sciences, 2025)
Modeling is important at the current stage of educational development. As a result of the radical change of educational paradigms, new requirements for modeling innovative pedagogical systems appear.